Development of creative abilities of preschool children - Sharieva Gavkhar (Euro Asian Journal Publishing, 2024)
Activities to develop the creative abilities of preschool children through games play an important role in the formation of a child's personality. At a young age, it is recommended to pay special attention to comprehensive development, that is, to the development of literary, artistic and musical abilities of preschool children.
Keywords: Pre-school education; children; creativity